The Impact of Cost Leadership Strategy and Financial Management Control System on Organizational Performance: An Empirical Investigation of Pakistani Service Sector - Ahmed Imran Hunjra; Farida Faisal; Faiza Gulshion (The Lahore Journal of Business)
The aim of this study is to check the impact of cost leadership strategy and financial management control system on organizational financial performance in Pakistani service sector. Questionnaire was used for data collection. Respondents were the finance managers of banking, insurance, and investment sectors companies listed with Karachi Stock Exchange. SPSS and AMOS were used to test the model. Confirmatory Factor Analysis was applied to check the validity of the instrument. Descriptive and inferential statistics were used for the analysis of data. The results show that there is significant and positive impact of cost leadership strategy and financial management control system on organizational financial performance. It is recommended that cost leadership strategy and financial management control system should be aligned on the long-term basis.